DJ-1 Mediates the Delayed Cardioprotection of Hypoxic Preconditioning Through Activation of Nrf2 and Subsequent Upregulation of Antioxidative Enzymes. Issue 2 (August 2015) - Yan, Yu-Feng; Chen, He-Ping; Huang, Xiao-Shan; Qiu, Ling-Yu; Liao, Zhang-Ping; Huang, Qi-Ren
Abstract : Abstract: We have recently shown that DJ-1 is implicated in the delayed cardioprotective effect of hypoxic preconditioning (HPC) against hypoxia/reoxygenation (H/R) injury as an endogenous protective protein. This study aims to further investigate the underlying mechanism by which DJ-1 mediates the delayed cardioprotection of HPC against H/R-induced oxidative stress. Using a well-characterized cellular model of HPC from rat heart–derived H9c2 cells, we found that HPC promoted nuclear factor erythroid 2–related factor 2 (Nrf2) and its cytoplasmic inhibitor Kelch-like ECH-associated protein-1 (Keap1) dissociation and resulted in increased nuclear translocation, antioxidant response element–binding, and transcriptional activity of Nrf2 24 hours after HPC, with subsequent upregulation of manganese superoxide dismutase (MnSOD) and heme oxygenase-1 (HO-1), which provided delayed protection against H/R-induced oxidative stress in normal H9c2 cells. However, the aforementioned effects of HPC were abolished in DJ-1–knockdown H9c2 cells, which were restored by restoration of DJ-1 expression. Importantly, we showed that inhibition of the Nrf2 pathway in H9c2 cells mimicked the effects of DJ-1 knockdown and abolished HPC-derived induction of antioxidative enzymes (MnSOD and HO-1) and the delayed cardioprotection. In addition, inhibition of Nrf2 also reversed the effects of restored DJ-1 expression on induction of antioxidative enzymes and delayed cardioprotection by HPC in DJ-1–knockdown H9c2 cells. Taken together, this work revealed that activation of Nrf2 pathway and subsequent upregulation of antioxidative enzymes could be a critical mechanism by which DJ-1 mediates the delayed cardioprotection of HPC against H/R-induced oxidative stress in H9c2 cells.